Influence of Ultraviolet Radiation on the Non-Enzymatic Antioxidant System in Fenugreek - Hamed M. El-Shora; Ryad A. Ghazy; Fathy A. El-Husseiny; Ghada E. Zaky; Aya A. Attya (American Journal of Bioscience and Clinical Integrity, 2026)
The present study indicates that UVC priming significantly enhances the accumulation of total phenols and α-tocopherol in germinated fenugreek seeds. This increase correlates with the upregulation of key phenylpropanoid pathway enzymes (PAL, CHS, CHI, and F3H), which are essential for flavonoid biosynthesis. Additionally, UVC treatment significantly elevated levels of vital antioxidants and osmoprotectants—including ascorbic acid, proline, and reduced glutathione (GSH)—resulting in correspondingly higher DPPH and ABTS radical-scavenging capacities. Finally, metabolic profiling revealed that UVC exposure effectively alters the phytochemical composition of the seeds, inducing the synthesis of novel metabolites while downregulating others.